Stability-indicating HPLC method optimization using quality by design with design of experiments approach for quantitative estimation of organic related impurities of Doripenem in pharmaceutical formulations - N. V. V. D. Praveen Boppy, Sharath Babu Haridasyam, Niroja Vadagam, Naveen Sara, Karthik Sara, Eswarlal Tamma (Journal of Applied Pharmaceutical Science, 2025)
Doripenem (DM), an antibiotic used for kidney, lung, and urinary infections, underwent the development of a robust high-performance liquid chromatography (HPLC) technique using the quality-by-design approach. This method, integrating design-of-experiments, detected organic impurities in both drug substances and formulated products. Operating with a C18 analytical column in a binary gradient mode with potassium phosphate buffer (pH 6.1) and acetonitrile as mobile phases, the method ran at a flow rate of 1.20 ml/minutes, with an injection volume of 20-μl and a column temperature of 45°C. Stability testing under various conditions, including hydrolysis, oxidation, heat, humidity, and light exposure, confirmed the method’s reliability without interference. Validation studies, compliant with ICH guidelines, revealed quantitation limits of 0.006%, linearity between 0.060 and 1.800 μg/ml (R2 > 0.999), and recoveries ranging from 96.8% to 99.1%. This HPLC method was effectively used for stability assessment in quality control testing, assessing doripenemic acid, doripenem assay, and organic impurities.
Keywords: Doripenem, organic related impurities, stress testing, design of experiments, stability-indicating method, high-performance liquid chromatography